Bridging Mathematical Modelling and Education for Sustainable Development in Pre-Service Primary Teacher Education - Neslihan Bulut; Rita Borromeo Ferri (Education Sciences, 2025)
This study examined the impact of a teacher training programme combining Education for Sustainable Development (ESD) and Mathematical Modelling (MM) on pre-service primary mathematics teachers’ (PSTs) understanding of sustainability and its integration into mathematics education. Using a mixed-methods approach, data were gathered through pre- and post-test questionnaires and qualitative reflections. The results showed a significant improvement in PSTs’ knowledge of sustainability after the training. Key themes included the development of mathematical modelling competence and an increased understanding of sustainability topics and the importance of critical thinking. Participants also emphasized the importance of lifelong learning, openness to change, and acquiring the necessary didactic skills for creating ESD–modelling tasks. Additionally, the study found that PSTs’ personal behaviours shifted toward sustainability, with a focus on responsible consumption, water conservation, and climate action, aligning with various Sustainable Development Goals (SDGs). The seminar addressed all 17 SDGs, however, in the post-test questionnaire, participants most frequently provided examples related to SDG 6 (Clean Water and Sanitation), SDG 12 (Responsible Consumption and Production), and SDG 13 (Climate Action). It recommended a stronger emphasis on interdisciplinary approaches, targeting underrepresented SDGs, and challenging existing beliefs that restrict sustainability integration in subjects like mathematics. Mathematical modelling activities were highlighted as a key tool for integrating sustainability concepts into mathematics lessons.